Influence of summer transhumance practice in the Carpathians, Apuseni Mountains, Romania, on cattle milk production and quality - Ranta, Mirela; Crișan, Ioana; Pleșa, Anca; Ihuț, Andrada (Frontiers in Animal Science, 2025)
In the Apuseni Mountains, a particular type of short-distance transhumance has been practiced for hundreds of years, in which people move a proportion of their cattle to grassland at higher altitudes, allowing them to save the hay from the grassland closer to home as winter fodder. This sustainable use of grassland is based on traditional practices. However, scientific research into the influence of this practice on milk production and quality is limited, an aspect analyzed in this study. The results showed that grasslands at higher altitudes have more limited biodiversity, and while the fat content increases, the milk production decreases. Pendular movement maintains grasslands in good condition and preserves cultural landscapes. This sustainable practice is still common in many mountainous regions today, providing economic benefits to local communities. During the summer months, some of the cattle herds are moved to mountain grazing areas (called temporary farms, TFs) in order to conserve the hay closer to home for winter fodder. This study investigated the impact of this practice on the milk yield and quality of Bălțată Românească tip Simmental cattle. All of the cattle included in the study were at the same stage of lactation at the start of the experimental period. The results showed that, during the summer months (June–August), the milk yield in the TF was significantly lower. However, the milk fat content was significantly higher in June and July, and a highly significant negative correlation was found between the milk yield and the milk fat content (rs = −0.94). The protein content of the milk was not significantly different between the permanent farm (PF) and the TF during the summer months. The PF grassland was more species-rich than the TF grassland. However, both were dominated by Poaceae species, and the forage quality parameters were not significantly different between farms. These results demonstrate that pendular movement causes moderate changes in milk production and composition, primarily due to variations in the forage quality and the pasture species composition. Pendular movement remains a sustainable grazing practice of ecological and economic importance to the mountain communities in the Apuseni Mountains. This type of pastoralism is still practiced in the mountain ranges of Europe and is closely linked to the lifestyle of mountain communities and contributes to their sufficiency.